2008
DOI: 10.1016/j.brainres.2008.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GABAA receptor α1 subunit mRNA and protein in rat neocortex following photothrombotic infarction

Abstract: Photothrombotic infarcts of the neocortex result in structural and functional alterations of cortical networks, including decreased GABAergic inhibition, and can generate epileptic seizures within one month of lesioning. In our study, we assessed the involvement and potential changes of cortical GABA A receptor (GABA A R) α 1 subunits at 1, 3, 7, and 30 days after photothrombosis. Quantitative competitive reverse transcription polymerase chain reaction (cRT-PCR) and semi-quantitative Western blot analysis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…In animal models, expression of GABA A receptor subunits shows a complex layer- and time-specific regulation after stroke. GABA A receptors generally decrease in perilesional cortical areas53270777879. Conversely, one recent report80 has shown that α1 subunit expression is increased in layer 5 after stroke and its activation using zolpidem improves recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, expression of GABA A receptor subunits shows a complex layer- and time-specific regulation after stroke. GABA A receptors generally decrease in perilesional cortical areas53270777879. Conversely, one recent report80 has shown that α1 subunit expression is increased in layer 5 after stroke and its activation using zolpidem improves recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Binary α1β3 receptors that are positively modulated by zolpidem may also have significant clinical effects in a number of neurological conditions where the ratio and location of various GABA receptor subunits are altered, for example, stroke 52 53 54 , or epilepsy 55 56 . Under these conditions, dramatic changes are occurring in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Results were standardized and presented as percentage change from the control value. Signals obtained in the same membrane but area different than bands were subtracted for background correction (Kharlamov et al 2008; Leung et al 2002). …”
Section: Methodsmentioning
confidence: 99%